2018
DOI: 10.1038/s41419-018-0818-0
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between hepatic tumor cells and macrophages via Wnt/β-catenin signaling promotes M2-like macrophage polarization and reinforces tumor malignant behaviors

Abstract: Tumor-associated macrophages (TAMs) are a major component of tumor microenvironment (TME) and play pivotal roles in the progression of hepatocellular carcinoma (HCC). Wnt signaling is evolutionarily conserved and participates in liver tumorigenesis. Several studies have shown that macrophage-derived Wnt ligands can activate Wnt signaling in tumor cells. However, whether Wnt ligands secreted by tumor cells can trigger Wnt signaling in macrophages is still elusive. In this study, we first verified that canonical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
168
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(190 citation statements)
references
References 49 publications
6
168
1
Order By: Relevance
“…In the absence of death/apoptotic signal to VECs, this provided a mechanism for the stimulation of VECs via macrophages and tumor angiogenesis (68). Also, Wnt ligands secreted by tumor cells could stimulate the polarization of TAMs to M2 subtype via the canonical Wnt signaling pathway, resulting in tumor growth and migration (69). Moreover, macrophage-derived soluble factors also induced canonical Wnt signaling pathway and promoted tumor growth and metastasis.…”
Section: Wnt Signaling and The Tumor Microenvironmentmentioning
confidence: 99%
“…In the absence of death/apoptotic signal to VECs, this provided a mechanism for the stimulation of VECs via macrophages and tumor angiogenesis (68). Also, Wnt ligands secreted by tumor cells could stimulate the polarization of TAMs to M2 subtype via the canonical Wnt signaling pathway, resulting in tumor growth and migration (69). Moreover, macrophage-derived soluble factors also induced canonical Wnt signaling pathway and promoted tumor growth and metastasis.…”
Section: Wnt Signaling and The Tumor Microenvironmentmentioning
confidence: 99%
“…Wnt-β-catenin signaling regulates macrophages functions, such as adhesion, migration and tissue recruitment (35,36) Wnt-b-catenin signaling promotes M2-like polarization of TAMs resulting in tumor growth, migration, metastasis, and immunosuppression (35,37,38) Wnts produced by macrophages drive contribute to tumor cell invasiveness and tumor growth (35,37,38)…”
Section: Wnt Signaling In Macrophagesmentioning
confidence: 99%
“…Tumorassociated macrophages (TAMs) play an important role in tumor progression and immune suppression (76)(77)(78). Wnts regulate macrophage functions, such as adhesion, migration, and tissue recruitment (35). In addition, it is well-documented that Wnts produced by macrophages is critical for tissue development and repair (35).…”
Section: Effects Of Wnts In Modulating Functions Of Other Immune Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…M2 polarization of TAMs is a multi-factor, multi-step and complex pathological process (13). Recent studies have shown that Wnt signaling plays a major role in M2-like TAMs polarization (14,15). Wnt5a, a member of Wnt family, binds to the frizzled receptor and LRP5/6 co-receptors to regulate multiple signaling pathways (16), thereby altering TME by inducing adipocytes to dedifferentiate into fibroblastlike cells or mesenchymal cells (17).…”
mentioning
confidence: 99%